Pengaruh Kemampuan Psikolinguitik terhadap Keterampilan Berbicara Siswa Menengah melalui Bimbingan dan Konsling Pendidikan Islam - Saiful Muktiali; Indriyani Achmad; Djoko Nugoroho (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This research aims to analyze the influence of psycholinguistic abilities on the speaking skills of Garuda Nusantara Vocational School students in Cikarang Selatan and explore the effectiveness of Islamic educational guidance and counseling in improving these two aspects. The approach used is quantitative with a quasi-experimental design, using Nonequivalent Control Group Design involving experimental and control groups. Data analysis techniques include t-tests to measure differences before and after intervention as well as regression analysis to see the relationship between research variables. The research results showed that there was a significant positive relationship between psycholinguistic abilities and students' speaking skills. Islamic educational guidance and counseling interventions provide a significant impact in improving speaking skills, especially in the aspects of clarity, thinking structure and politeness of communication. Statistical analysis showed a significant increase in the experimental group compared to the control group, with a p-value <0.05. In addition, the regression results show that 92.10% of the variation in speaking skills can be explained by psycholinguistic abilities. Thus, this research confirms the importance of developing guidance and counseling programs based on Islamic values ​​in improving secondary students' speaking skills.